Evaluation of sleep characteristics of children and adolescents with type 1 diabetes mellitus - Silva,Renata Aparecida e (2022)
ABSTRACT Objective: To evaluate sleep characteristics of children and adolescents with type 1 diabetes mellitus (T1DM) and their relationship with glycemic control. Methods: A cross-sectional study was conducted at a public hospital in São Paulo, Brazil. It included 86 patients with T1DM, aged between 10 and 18 years old, who were on insulin therapy, had performed at least three measurements of capillary blood glucose throughout the day, and had normal thyroid function. The clinical, anthropometric, and laboratory data of each patient were evaluated. The Pediatric Daytime Sleepiness Scale (PDSS) and the Munich Chronotype Questionnaire (MCTQ) were used to assess the sleep characteristics. Results: The mean level of glycated hemoglobin (HbA1c) was 9.2±2.1%, and it was higher in adolescents than in children. The mean score of PDSS was 13.9±4.7. Patients with HbA1c<7.5% had lower PDSS scores and longer sleep duration on weekdays than patients with HbA1c≥7.5%. HbA1c levels were negatively correlated with chronotype values and sleep duration on weekdays and positively correlated with social jet lag. Patients who had had T1DM for less than three years had a higher prevalence of daytime sleepiness. The regression analysis showed that higher HbA1c (≥7.5%) and shorter time since the diagnosis of T1DM increased the chance of daytime sleepiness, regardless of age and sex. Conclusions: Patients with higher HbA1c had more daytime sleepiness, a morning chronotype, shorter sleep duration on weekdays and a more significant social jet lag. The shorter diagnosis time for T1DM and greater levels of HbA1c increased the chance of daytime sleepiness.